QUALITY AND MAIN INDICATORS OF ELECTRONIC TEXTBOOKS IN THE FORM OF MULTIMEDIA - Bunyodjon A’zamov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article presents the advantages, quality level, and aspects of using a multimedia e-textbooks